The Psychological Well-Being of Qur'an Memorization Students in Islamic Boarding Schools in Relation to Academic Stress - Masrifah, Masrifah; Wahyuni, Hera; Astuti, Jayaning Sila (Universitas Muhammadiyah Sidoarjo, 2024)
Students memorizing the Qur'an face a variety of complex challenges. Those who effectively manage these demands are likely to experience positive psychological conditions and optimal psychological well-being. This study aims to investigate the impact of academic stress on the psychological well-being of students memorizing the Qur'an in Islamic boarding schools. Using a quantitative approach with a correlational design, the sample consisted of 100 Qur'an memorization students at the Bangkalan Madura Islamic boarding school, selected through accidental sampling. The study utilized Ryff's psychological well-being scale (reliability 0.914) and Sarafino and Smith's academic stress scale (reliability 0.802). Data were analyzed for normality, linearity, and heteroscedasticity using the Kolmogorov-Smirnov test, followed by hypothesis testing through simple linear regression analysis. The results indicated that academic stress significantly influences psychological well-being (F = 10.248, p = 0.001). Academic stress accounts for 30.2% of the variance in psychological well-being, with the remainder influenced by other factors.